National Gastronomy and Gastronomic Tourism of Montenegro on its Way to the European Union - Vujačić Vesna; Kukanja Marko; Janinović Jovana (EU agrarian Law)
Montenegro, a Mediterranean gem, boasts abundant natural and cultural treasures, forming the bedrock of its thriving tourism industry. Among its various tourism branches – cultural, nautical, health, and MICE – gastronomy stands out as a potent driver. The indigenous gastronomic landscape not only entices foreign tourists but also fuels increased consumption. This paper endeavours to elucidate the justification and potential of Montenegro’s gastronomic tourism by spotlighting its national gastronomy. Gastronomy, intricately linked with destination identity, plays a pivotal role in shaping the destination’s image. Drawing inspiration from the Republic of Slovenia’s successful declaration as a European gastronomic region in 2021, this paper advocates for a similar trajectory for Montenegro to enhance its tourism brand recognition.